Linguistic and Cultural Problems in Javanese-English Subtitle of CAPCIPTOP! Short Movie - Priska Meilasari (Faculty of Humanities, Universitas Jenderal Soedirman, 2022)
The presented paper is focusing on the Javanese-English subtitle. The data involve a culture-bound short movie entitled “CAPCIPTOP!” uploaded on Youtube by Ravacana Film. The samples of this study are fifteen students joining subtitling class in the even semester of the academic year 2020/2021 at Widya Mandala Catholic University. The research findings show that students are facing two common problems namely linguistic and cultural problems in subtitling Javanese to English. Those problems are crucial as they are closely related to how a translator transfers messages from Javanese to English completely and minimize the misunderstanding among the viewers. This study is concluded with some suggestions for students in dealing with the problems in Javanese-English subtitling.